Traduire le théâtre de Gil Vicente, spécificités de traduction et possibles apports liés à l’intelligence artificielle - Gonçalves, Philippe-Alexandre (Studia Romanica Posnaniensia, 2024)
Translating the theater of Gil Vicente poses a significant challenge, that only specialists about the author, with some rare exceptions, have translated his plays. Between the nuances of the text, the archaisms of the language, and the specificities of theatrical writing, this playwright has seen few of his plays, also known as autos, translated into French. At a time when the relationship between the translator and technological advancements is becoming increasingly intertwined, it is important to analyze how certain software, particularly those of Artificial Intelligence, perform in the task of translation and what their impact might be on future translations of Gil Vicente.